Analysis of MSMEs in Tasikmalaya City Based on Business Characteristics and Scale - Sukmawati, Heni; Nasution, Fatimah Zahra; Wisandani, Iwan; Mutmainah, Luliyatul (JURNAL EKONOMI SYARIAH, 2024)
Introduction to The Problem: The role of MSMEs in the Indonesian economy is very important, including contributing to labor absorption, driving economic growth, GDP and investment as well as economic equality. However, there is a gap in information about MSMEs regarding their characteristics, business scale and distribution, causing information regarding MSMEs to be less detailed, less up to date and difficult to obtain for the development of MSMEs themselves.Purpose/Objective Study: This research aims to collect and analyze data on MSMEs in Tasikmalaya City based on their characteristics and business scale.Design/Methodology/Approach: This research method was carried out using a qualitative descriptive approach. This research collected primary data through interviews and questionnaires and secondary data through databases from related agencies and the entrepreneurial community in Tasikmalaya City. After that, the data is verified and classified based on the characteristics and scale of the business which is presented in table and info graphic form.Findings: This research finds that the number of MSMEs in Tasikmalaya City obtained from primary and secondary data in 2023 will reach 3751 MSMEs. However, only a small portion of MSMEs have complete data and information. The district with the largest number of MSMEs is Cihideung District with 2761 MSMEs and the district with the smallest number of MSMEs is Purbaratu District with 7 MSMEs. The three most common types of business fields are trade, industry and services. The results of this research can be used as information in making decisions regarding MSME research and development programs in Tasikmalaya City.Paper Type: Research ArticleKeywords: MSMEs; Characteristics; Business Scale; Development